1998
DOI: 10.1002/malq.19980440309
|View full text |Cite
|
Sign up to set email alerts
|

Versions of Normality and Some Weak Forms of the Axiom of Choice

Abstract: We investigate the set theoretical strength of some properties of normality, including Urysohn's Lemma, Tietze-Urysohn Extension Theorem, normality of disjoint unions of normal spaces, and normality of F, subsets of normal spaces.Mathematics Subject Classification: 03325, 04A25, 54D10, 54D15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…Hence, by the Tietze extension theorem which holds in ZF (see e.g. [3,Lemma 2]), h extends to a continuous real valued g on X. By our hypothesis, ρ(g(A), g(B)) = 0.…”
mentioning
confidence: 79%
“…Hence, by the Tietze extension theorem which holds in ZF (see e.g. [3,Lemma 2]), h extends to a continuous real valued g on X. By our hypothesis, ρ(g(A), g(B)) = 0.…”
mentioning
confidence: 79%
“…Of course, every T space is a U space and all U spaces are normal. In [16], NU (NT, resp.) is an abbreviation to: "Every normal space is a U space."…”
Section: Strange Hausdorff Compactificationsmentioning
confidence: 99%
“…Hence, in ZF + DC, a topological space X satisfies UL(X) if and only if TET(X) holds. In [16], it was shown that there is a model M of ZF in which there is a compact Hausdorff space X such that UL(X) holds and TET(X) fails in M. However, it is an open question, already posed in [16], whether UL implies TET.…”
Section: Strange Hausdorff Compactificationsmentioning
confidence: 99%
See 2 more Smart Citations